2012
DOI: 10.1089/cyber.2011.0583
|View full text |Cite
|
Sign up to set email alerts
|

Defending the Doomed: Implicit Strategies Concerning Protection of First-Person Shooter Games

Abstract: Censorship of violent digital games, especially first-person shooter (FPS) games, is broadly discussed between generations. While older people are concerned about possible negative influences of these games, not only players but also nonplayers of the younger net-generation seem to deny any association with real aggressive behavior. Our study aimed at investigating defense mechanisms players and nonplayers use to defend FPS and peers with playing habits. By using a lexical decision task, we found that aggressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…One possible explanation for the discrepant views is mostly ignored: age differences and therefore generation conflicts. While the older generation is concerned about an increase of anti-social behavior and emotional instability due to violent games with which they are unfamiliar, young players tend to be skeptical of negative effects potentially to defend their identity as gamers (Kneer, Glock, Beskes, & Bente, 2012;Kneer, Munko, Glock, & Bente, 2012). Perception on the other hand is also influenced by experience/expertise with a subject (Greenwald & Banaji, 1995) and guided by pre-existing attitudes and knowledge (Greenwald et al, 2002;Shiffrin & Schneider, 1977).…”
Section: Discussion About Violent Video Games and Research Questionsmentioning
confidence: 99%
See 1 more Smart Citation
“…One possible explanation for the discrepant views is mostly ignored: age differences and therefore generation conflicts. While the older generation is concerned about an increase of anti-social behavior and emotional instability due to violent games with which they are unfamiliar, young players tend to be skeptical of negative effects potentially to defend their identity as gamers (Kneer, Glock, Beskes, & Bente, 2012;Kneer, Munko, Glock, & Bente, 2012). Perception on the other hand is also influenced by experience/expertise with a subject (Greenwald & Banaji, 1995) and guided by pre-existing attitudes and knowledge (Greenwald et al, 2002;Shiffrin & Schneider, 1977).…”
Section: Discussion About Violent Video Games and Research Questionsmentioning
confidence: 99%
“…Playing expertise as well as age led to defensive reactions in game studies of players -in case players were confronted with the common belief that violent video games are dangerous (Kneer, Munko, et al, 2012). Interestingly enough, not only players but young non-players also defended video games in order to protect a famous activity among their peers.…”
Section: Perception Of Games Effects and Playersmentioning
confidence: 99%
“…Among both clinicians (Ferguson, ) and the general public (Przybylski, ), age is a strong predictor of negative attitudes about video games. In fairness, biases may work in both directions with younger people defensive about their hobby (Kneer, Munko, Glock, & Bente, ), just as older people may be reflexively hostile toward it. However, this may have less to do with age, per se, but rather the selective exposure of individuals of different ages to new media.…”
Section: A Brief History Of Video Game Debatesmentioning
confidence: 99%
“…The importance of considering motivational aspects in digital game effects was underlined by Denzler, Häfner, and Fçrster (2011) who found that when playing a violent game with the goal to vent anger, accessibility of aggressive thoughts (measured with lexical decision tasks) was actually inhibited. Kneer, Munko, Glock, and Bente (2012) showed that young adults suppressed aggressive concepts when primed with violent game content as an implicit defense mechanism for their own gaming habits or even those of the generation they belong to (see also Kneer, Glock, Beskes, & Bente, 2012). Thus, many investigations found that violent content in games increases the accessibility of aggressive thoughts.…”
Section: Aggressive Cognitionsmentioning
confidence: 99%